2021
DOI: 10.33258/birci.v4i1.1636
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Product Promotion and Innovation Activities on Marketing Performance in Middle Small Micro Enterprises in Cianjur

Abstract: This study aims to determine the effect of promotional activities and product innovation on marketing performance in Micro, Small and Medium Enterprises in Cianjur. The method used is explanatory research with analysis techniques using statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this study that promotional activities have a significant effect on marketing performance by 40.0%, hypothesis testing is obtained t count> t table or (7.915> 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 1 publication
0
5
0
1
Order By: Relevance
“…Some businesses even find new product categories such as frozen food, new menu variations and so on. Such examples illustrate innovations in the field of marketing that have an impact on company performance (Nurjaya et al, 2021). However, the average result is that the innovations carried out are not the radical ones, and this can be seen from the average results of X2.3 statement, that the innovations carried out do not disrupt the market.…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…Some businesses even find new product categories such as frozen food, new menu variations and so on. Such examples illustrate innovations in the field of marketing that have an impact on company performance (Nurjaya et al, 2021). However, the average result is that the innovations carried out are not the radical ones, and this can be seen from the average results of X2.3 statement, that the innovations carried out do not disrupt the market.…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…The results indicated that as an advertising platform, Facebook is highly effective in creating product promotions. This was notably revealed by the study of Nurjaya et al (2021). Product promotion and other promotional activities have a strong relationship with the marketing effectiveness of businesses, specifically in advertising.…”
Section: Highly Effectivementioning
confidence: 93%
“…Umumnya, produk dalam negeri yang berhasil menembus pasar internasional disebut sebagai produk go international. Hal ini dicapai melalui promosi dimana menurut Nurjaya et al, (2021) promosi sangat berperan penting dalam kinerja pemasaran usaha. Meskipun Indonesia sudah banyak memiliki UKM dengan produk go international ternyata banyak yang belum mampu menembus pasar luar negeri.…”
Section: Pendahuluanunclassified